Taking the temperature of Earth’s hottest crust - Korhonen, Fawna; Clark, Christopher; Brown, M.; Taylor, Richard (Elsevier Science BV, 2014)
The limitations of conventional thermobarometry and petrogenetic grids for determining the peak P–T conditions of granulites are well known. These limitations have been overcome during the past decade with the calibration of single mineral thermometers, particularly Al-in-orthopyroxene, Zr-in-rutile and Ti-in-zircon, and the increased use of P–T pseudosection thermobarometry. Most recent studies of ultrahigh temperature (UHT) granulites (those formed at >900°C) have used one or other of these methods to argue for peak metamorphic temperatures up to or beyond 1000°C. Since models for the thermal evolution of orogens generally do not predict such extreme temperatures it is important to confirm their veracity. Here we combine in a single study single mineral thermometry with P–T pseudosection thermobarometry to provide a robust determination of peak temperature and tight constraints on the retrograde P–T path for one UHT granulite locality in the Eastern Ghats Province. This is the first study to apply the most recent update of the internally consistent thermodynamic dataset of Holland and Powell (2011) and the re-parameterized a–x models of White et al. (2014) and Wheller and Powell (2014) to UHT granulites. For two samples, we report Zr-in-rutile temperatures of >1000°C and Ti-in-zircon temperatures of ~900°C, supported by Al-in-orthopyroxene temperatures of ~900?C, that correspond closely to those estimated using P–T pseudosections for conditions at the thermal peak and at the solidus on the retrograde P–T path, respectively. The P–T path is counter-clockwise in common with other UHT granulite localities in the Eastern Ghats Province. By demonstrating that UHT metamorphism at T >1000°C is real we provide a robust constraint that must be met by geodynamic models for the development of ultrahot orogens.